2016
DOI: 10.4103/2277-9175.178785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver enzymes level and sonographic findings value with liver biopsy findings in nonalcoholic fatty liver disease patients

Abstract: Background:This study aimed to examine the relationship between sonographic diagnosis of fatty liver and liver enzyme level with histopathologic abnormalities and liver biopsy findings in patient with the nonalcoholic fatty liver disease (NAFLD).Materials and Methods:This cross-sectional study conducted on 109 patients with diagnosed and under treatment NAFLD refer to Gastroenterology Clinics of AL Zahra Hospital in Isfahan, Iran. Age, sex, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The serum ALT is known to rise with the degree of hepatic steatosis among nonpregnant population [37]. Further, the serum ALT level during the third trimester of pregnancy is known to be lower than the nonpregnant women[38].…”
Section: Discussionmentioning
confidence: 99%
“…The serum ALT is known to rise with the degree of hepatic steatosis among nonpregnant population [37]. Further, the serum ALT level during the third trimester of pregnancy is known to be lower than the nonpregnant women[38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the rats fed on GT oligosaccharides(HFD + O100, HFD + O200) increased plasma HDL concentration and it seems that the GT oligosaccharides regulate HDL concentration by lipid catabolism, as HDL can transport cholesterol from peripheral tissues to the liver for oxidation (Muanprasat & Chatsudthipong, 2017;Tao et al, 2019). In accordance with decreased total triglycerides, cholesterol, and re- HOSSEIN ZADEH et al Khodadoostan et al, 2016;Taliercio et al, 2013). Our finding showed that the using of GT oligosaccharides lower HFD induced high plasma concentration of ALT and AST, indicating that administration of GT oligosaccharides protect our rats against HFD induced liver damage.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, our findings indicated that the rats fed HFD showed significantly higher plasma concentration of ALT and AST compared to the control and GT oligosaccharides groups. ALT and AST are known an important biomarkers related to hepatocytes function, and the increased plasma concentration of aforementioned enzymes implied occurrence of Cholestasis, imbalance of lipid and carbohydrate metabolism, hepatotoxicity and hepatocytes injury, which are associated with NAFLD and hyperlipidemia (Chang et al, 2013; Khodadoostan et al, 2016; Taliercio et al, 2013). Our finding showed that the using of GT oligosaccharides lower HFD induced high plasma concentration of ALT and AST, indicating that administration of GT oligosaccharides protect our rats against HFD induced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of liver cell damage, the concentration of liver enzymes (ALT, AST), amylase, and ALP increase in plasma [ 42 ]. ALP is a membrane hydrolysis enzyme that is used as a biomarker for cholestasis, which is caused by hepatic steatosis and a lipid-carbohydrate metabolic imbalance [ 46 , 47 ]. An increase above parameters stimulates proinflammatory cytokines (TNF-ɑ and IL-6) in the bloodstream, resulting in reduced lipid degradation and increase accumulation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%